"Exercícios de raciocínio" em três linguagens: ensino de física nas séries iniciais - Maria da Conceição Barbosa Lima; Anna Maria Pessoa de Carvalho (Ensaio Pesquisa em Educação em Ciências, 2002)
In order to study the fitness of child's tales as a Physic Teaching instrument, we elaborated a science learning activity to second grade students of an elementary public school in São Paulo city. After reading a tale, a logical thought exercise was discussed in small groups of students, without any stimulation to any kind of experimentation. After this, children were invited to discuss their ideas in a big circle, composed by all the students of the class. Finally, they were asked to report individually their ideas and/or conclusions about the class activity, using drawings and/or small wordings. This work presents the analysis of their talk during the circle discussion, as well as analysis of their writings.